2021
DOI: 10.1111/1468-2230.12628
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Implementing Anti‐Money Laundering Regulation: An Empirical Analysis

Abstract: For over three decades, money laundering has been an area of concern for policymakers and law enforcement, with significant efforts undertaken at national and international levels to combat it. Recently, laundering of criminal proceeds using real property has attracted increased attention amongst policymakers. Various efforts are now being undertaken to tackle money laundering in the UK property market, but there are still significant difficulties in its practical implementation. Drawing upon semi-structured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Researchers have observed that inter-agency coordination and collaboration for AML compliance and AML regulations are essential to detecting and preventing money laundering (Loh 2021;Zavoli and King 2021;Ofoeda et al 2022). Effective collaboration between AML compliance and AML enterprises can promote a unified approach to curbing money laundering while helping to create an environment of mutual trust among law enforcement, banks, and other involved institutions (Ofoeda et al 2022;Zavoli and King 2021;Lokanan 2022). Collaborative efforts can ensure that companies and organizations comply with applicable AML legal requirements, further strengthening domestic and international AML defenses (Chen et al 2018;Masciandaro and Filotto 2001).…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Researchers have observed that inter-agency coordination and collaboration for AML compliance and AML regulations are essential to detecting and preventing money laundering (Loh 2021;Zavoli and King 2021;Ofoeda et al 2022). Effective collaboration between AML compliance and AML enterprises can promote a unified approach to curbing money laundering while helping to create an environment of mutual trust among law enforcement, banks, and other involved institutions (Ofoeda et al 2022;Zavoli and King 2021;Lokanan 2022). Collaborative efforts can ensure that companies and organizations comply with applicable AML legal requirements, further strengthening domestic and international AML defenses (Chen et al 2018;Masciandaro and Filotto 2001).…”
Section: Related Workmentioning
confidence: 99%
“…The key takeaway from the literature is that SARs can be incredibly useful in detecting money laundering signs. However, this is only true when SARs are used with additional measures such as transaction monitoring, CDD, and KYC (Singh and Best 2019;Lokanan 2022;Zavoli and King 2021). This underscores the need for multiple layers of defense to stay ahead of money launderers' attempts to infiltrate financial systems (Lokanan 2022;dalla Pellegrina et al 2020;Ketenci et al 2021).…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations